Changements des gestes professionnels des enseignants du présentiel au distanciel - Chaymae Aberkane; Sara El Mouhsine; Toufik Azzimani (Distances et Médiations des Savoirs)
The year 2020 was marked by the health crisis caused by COVID-19, and as a result, the sudden switch from a face-to-face learning teaching modality to a totally distance learning one was imposed. This change of modality placed the actors involved in an unprecedented situation, in which they were encouraged to adapt their teaching practices, in particular their professional gestures, to a totally online teaching modality. The aim of this study is first to identify the difficulties encountered by teachers in coping with this change, and then to assess the impact of this teaching mode on their professional gestures, in the light of Jorro’s model (2005). To this end, we opted for qualitative research carried out through semi-directive interviews with forty teachers belonging to the different establishments of Mohammed First University. These teachers expressed difficulties in implementing professional gestures in a distance learning context. This subsequently led to changes in the appearance and suppression of certain gestures.